2013
DOI: 10.1080/14427591.2013.804619
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Time and Occupation: Experiences of People with Chronic Fatigue Syndrome/Myalgic Encephalomyelitis

Abstract: Chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is a disabling condition that disrupts the normal rhythms and activity patterns of daily life. Although temporal dimensions such as time use, tempo and temporality have an important relationship to occupation there has been limited study of these factors within CFS/ME. This qualitative study explored how people with CFS/ ME perceived the relationship between time and occupation through the experience of their illness. A social constructivist approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Participants also had difficult matching their capacity for activity with their expectations, having developed a norm of high activity prior to illness. Therefore, using activity diaries may be helpful in enabling people to align time to activity [55]. However, if underlying beliefs about activity are not addressed then these may be experienced as frustrating, as Ann felt this illustrated her lack of activity in comparison to past levels.…”
Section: Implications Of Activity Patterns During Cfs/me For Rehabilimentioning
confidence: 93%
“…Participants also had difficult matching their capacity for activity with their expectations, having developed a norm of high activity prior to illness. Therefore, using activity diaries may be helpful in enabling people to align time to activity [55]. However, if underlying beliefs about activity are not addressed then these may be experienced as frustrating, as Ann felt this illustrated her lack of activity in comparison to past levels.…”
Section: Implications Of Activity Patterns During Cfs/me For Rehabilimentioning
confidence: 93%
“…Furthermore, adjusting the tempo of action and matching time allocation and task performance can be used to diminish time pressure and support the sustainability of occupations (Pemberton & Cox, 2013). Synchronisation also recognises the importance of temporality and narrative, giving time to grieve for a past active identity and transition to new values and future vision, more congruent with continuing wellbeing.…”
Section: The Conceptualisation Of Synchronisingmentioning
confidence: 99%
“…Wilcock (1999) previously proposed that there is a present day imbalance in doing, with some people doing too much, and that harmony is needed between doing well, well-being and becoming healthy. We have shown that disruptions of time use, tempo and temporality are experienced by people with chronic fatigue (Pemberton & Cox, 2013). Others have identified that there is increasing time pressure as every moment of the day fills with constant activity (Larson & Zemke, 2003;Roxburgh, 2004) and increasing speed (Darier, 1998;Tranter, 2013).…”
mentioning
confidence: 99%
“…In a study of individuals with chronic fatigue syndrome, participants used the metaphor of 'burning the candle at all four ends' to describe their experience of the illness, the role of time, and their need to participate in occupations with a new, conscious slowness (Pemberton & Cox, 2013). Wright-St Clair (2003) found that participants used metaphor as a tool to create and express meaning through rich imagery, which helped them to transform both their illness and their illness experience following a diagnosis of multiple sclerosis.…”
Section: Current Metaphors Used In Occupational Sciencementioning
confidence: 99%